Hybrid gravimetry monitoring of Soultz-sous-Forêts and Rittershoffen geothermal sites (Alsace, France). (November 2018) - Portier, Nolwenn; Hinderer, Jacques; Riccardi, Umberto; Ferhat, Gilbert; Calvo, Marta; Abdelfettah, Yassine; Heimlich, Christine; Bernard, Jean-Daniel
Highlights: Three year time-lapse gravity monitoring of two Alsatian geothermal reservoirs. Vertical deformation measured by leveling study and related to gravity changes. Differential gravity signal in agreement with the injection and extraction positions. Abstract: We investigate the feasibility of the hybrid gravity technique applied to two geothermal reservoirs in northern Alsace, France, namely the Soultz-sous-Forêts and Rittershoffen sites. Soultz-sous-Forêts site is the first enhanced geothermal system demonstration site producing electricity in France. Here a geothermal fluid at 165 °C allows to produce around 1.5 MW thanks to one injection well and one production well 5 km deep. Rittershoffen site is dedicated to an industrial use and it is designed to produce 24 MWth heat power with 2 wells around 2.5 km deep. The most recent production episodes of Rittershoffen and Soultz-sous-Forêts geothermal plants have started respectively on May and June 2016. To study underground mass redistribution, time-lapse relative microgravity measurements have been done since 2014 on a network designed ad hoc for Soultz-sous-Forêts site and since 2015 for Rittershoffen site. After tide and drift correction, double differences are calculated to retrieve the gravity variation at each measuring point compared to a reference time and station. Absolute gravity measurements have been also collected at one of the reference stations. Before the beginning of the production in 2016, the stability of the Soultz-sous-Forêts reference station was monitored through the repetition of absolute measurements and continuous gravity records. In 2016, regular ties between the reference stations and the Strasbourg gravity observatory STJ9 have been done. Several superconducting gravimeters operate continuously in STJ9. Thus, we approach the concept of hybrid gravity. Vertical deformation is also controlled thanks to six continuous GPS measurements: the height changes are less than 1 cm. So we consider that our gravity variations are only due to subsurface mass changes. For the Soultz-sous-Forêts network, we notice significant changes in agreement with the position of the injection and the production wells. The maximum gravity change is 31 ± 8 μGal. On the contrary, we do not detect any similar signal for the Rittershoffen network. A simplistic model using two spherical sources located at 5 and 2 km for Soultz-sous-Forêts and Rittershoffen sites respectively shows negligeable surface gravity changes when taking into account the known injection and production flow rates.